1967
DOI: 10.1099/00221287-49-3-401
|View full text |Cite
|
Sign up to set email alerts
|

Cultural Characters and Serological Relationships of Some Mycoplasmas Isolated from Bovine Sources

Abstract: Cultural characteristics and serological relationships of mycoplasmas from the bovine vagina, mastitic milk, and other sources were studied. Parasitic strains could be distinguished from saprophytic strains in that they required incorporation of horse serum into the PPLO agar for growth, produced surface crystallization on PPLO agar and did not ferment carbohydrates. All strains were haemolytic for red blood cells of the guinea pig, rabbit, sheep, cow and horse. Satellite growth enhancement was seen only with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
17
0
1

Year Published

1970
1970
2024
2024

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(18 citation statements)
references
References 5 publications
0
17
0
1
Order By: Relevance
“…Sintomas semelhantes foram descritos por Jain et al (1967), Boughton (1979) e Jasper (1982. Duas vacas que ficaram sob observação por seis meses apresentaram anorexia com perda progressiva de peso.…”
Section: Resul Resul Resul Resul Results T T T Tados E Discus Ados E Dunclassified
“…Sintomas semelhantes foram descritos por Jain et al (1967), Boughton (1979) e Jasper (1982. Duas vacas que ficaram sob observação por seis meses apresentaram anorexia com perda progressiva de peso.…”
Section: Resul Resul Resul Resul Results T T T Tados E Discus Ados E Dunclassified
“…To involve in the studies a special reference strain for M . bouirnastitidis, however, does seem to blur the issue, which is simply a question of classification and nomenclature of a certain group of mycoplasmas, as pointed out by Jain et al (11). The serological identity of different strains within this group has never been disputed (1, 2, 14), notably not by Jain et al (ll), who, as mentioned previously, also compared strains Donetta and California 01.…”
mentioning
confidence: 85%
“…They concluded that some strains, including Donetta (synonymous with rrConnecticut"), California 01, and Widanka, formed a homogenous and distinct group as determined by double immunodiffusion and growth inhibition tests. Jain et al (11) did not find the name M . agalactiae subsp.…”
mentioning
confidence: 99%
See 2 more Smart Citations